Low-temperature-resistant sugars in avocado rootstocks - Bernal-Valenzo, Bernardo; Calderón-Zavala, Guillermo; López-Jiménez, Alfredo; Padilla-Chacon, Daniel (Revista Mexicana de Ciencias Agrícolas, 2024)
In Mexico, due to the demand for fruit, orchards of avocado (Persea americana Mill.) variety ‘Hass’ of subtropical climate are erroneously established in cold areas, affecting their production; an alternative is to use cold-tolerant rootstocks of the Mexican race, tolerance related to the increase of sugars in areas of demand, which it shares through grafting with the ‘Hass’ variety; therefore, in 2021, the segregants of the ‘rootstocks’ duke 7, tepetl, aceitoso, and colecta 1 were evaluated at the College of Postgraduates; analyzing glucose, fructose, sucrose and starch contents in vegetative shoots at 1, 7, and 14 days of treatment; in chamber 1 (treatment) with luminosity of 380 μmol m-2 s-1 and temperatures with light of 15.61 °C, and darkness of 4.40 °C; and chamber 2 (control) with luminosity of 367 μmol m-2 s-1 and temperatures with light of 23.2 °C, and darkness of 19.29 °C, considering the factor of cold and low luminosity, it was observed that, chlorophyll in the leaves shows growth without photosynthetic deficiency in plants in both chambers; the glucose content of the ‘Hass’ variety varies according to the glucose content in the rootstock; the fructose content increases in grafted and non-grafted materials, acting as an osmoprotectant, the sucrose content increases in the grafted aceitoso material and the starch content is not affected; as a result, duke 7 and tepetl were the materials with the highest concentration of glucose and fructose under cold conditions.
Keywords: cold tolerant; fructose; glucose; ‘Hass’; segregating